Cost-Outcome and Cost-Effectiveness Analysis: Emerging Nonprofit Performance Evaluation Techniques. - Sorensen, James E.; Grove, Hugh D. (The Accounting Review, 1977)
ABSTRACT: Starting with the increased role of nonprofit organizations and mounting pressures for accountability, this paper reviews several contemporary approaches used to achieve performance evaluation in nonprofit service organizations. An analysis of the deficiencies of social indicators, PPB systems and cost-benefit analysis leads to prospective cost-analytic solutions focusing upon costs and outcomes of service programs. In developing these solutions, cost-outcome is emphasized as fundamental to building viable cost-effectiveness analyses for service program evaluation and accountability. Conceptual discussions of related outcome issues follow. A detailed mental health example illustrates the application of the combined cost-outcome and cost-effectiveness methodology in assessing nonprofit performance for decision-making purposes.